Correlations of Theory of Mind Deficits with Clinical Patterns and Quality of Life in Schizophrenia - Urbach, Mathieu; Brunet-Gouet, Eric; Bazin, Nadine; Hardy-Baylé, Marie-Christine; Passerieux, Christine (Frontiers in Psychiatry, 2013)
Background: Numerous studies have demonstrated the existence of theory of mind (ToM) impairments in patients with schizophrenia. The clinical consequences of these impairments are currently under debate. Accumulated evidence suggests that ToM deficits are linked to negative and disorganization symptoms, but direct correlations are lacking. Moreover, it is unclear whether ToM deficits are related to reduced quality of life (QoL). Methods: To extend the understanding of objective (i.e., clinical symptoms) and subjective (QoL) correlates of impaired ToM, we assessed 206 patients with schizophrenia based on performance of an ecological task (Versailles-Situational Intention Reading, V-SIR), a Communication Disorders Scale (SCD), the Positive and Negative Syndrome Scale (PANSS), the Clinical Global Impression rating, and a QoL questionnaire (S-QoL). Statistical inferences were drawn from correlations analyses considering both factors/subscales aggregates and single items. Results: ToM performance was negatively correlated to disorganization and negative PANSS factors. Poor V-SIR performance was correlated with “conceptual disorganization”, “difficulties in abstract thinking” and “apathy/social withdrawal”. The SCD was correlated with “negative”, “disorganization”, and “anxiety/depression” PANSS factors. The S-QoL total score was not significantly correlated with ToM performance. Only the item “difficulties in expressing feelings” was significantly correlated with poorer V-SIR performance. Conclusions: We discuss the intriguing paucity of the results and what they reveal about the difficulties faced by psychiatrists with patients not expressing complaints about lack of social skills.